Dariusz Brodka y Joanna Janik-Sławomir Sprawski (eds.), Freedom and Its Limits in the Ancient World, Cracovia, Jagiellonian University Press, 2003 (= Electrum. Studia z historii starożytnej, vol. 9) (Minerva, 2019)
Review: Dariusz Brodka y Joanna Janik-Sławomir Sprawski (eds.), Freedom and Its Limits in the Ancient World, Cracovia, Jagiellonian University Press, 2003 (= Electrum. Studia z historii starożytnej, vol. 9)